Oral Hygiene Practices among Saudi Arabian Children and Its Relation to Their Dental Caries Status - M. F. A. Quadri; M. A. Shubayr; A. H. Hattan; S. A. Wafi; A. H. Jafer (International Journal of Dentistry)
Dental caries is one of the most common preventable diseases occurring among children. The aim here is to survey the oral hygiene practices that are commonly followed by Arab children and to see its relationship with their dental caries status. A cross-sectional study with multistage random sampling technique was conducted. Sociodemographic data and information on oral hygiene practices like use of toothbrush, dental floss, siwak, frequency of brushing along with number of snack between meals per day, and consumption of sugar per day was obtained. Presence of plaque on tooth surfaces was reported using plaque index, which was followed by DMFT index to determine the dental caries status. Among the sample of 500 school children, the mean plaque score in male (mean = 0.69; SD = 0.50) was slightly higher than the female (mean = 0.66; SD = 0.46). Increased frequency of snacks (P=0.05; ß=0.08; CI = −0.00, 0.09) and sugar consumption (P=0.01; ß=0.16; CI = 0.04, 0.27) per day significantly showed higher values of DMFT. Also, the odds of dental caries among the school children who were irregular in brushing their teeth was higher in contrast to the children brushing once (P=0.03; OR = 0.89; CI = 0.70, 1.12) or twice (P=0.03; OR = 0.80; CI = 0.64, 0.93) per day. It is recommended that the dental public health practitioners here should consider the effect of oral hygiene practices on oral health status in order to design the future health promotion interventions.